Experimental Characterization of Glass/ Carbon Hybrid Composite Reinforced by SiO2 Nanoparticles - Thaker S. Dawood; Basim M. Fadhil; Dlair O. Ramadan (Tikrit Journal of Engineering Sciences)
The proven optimal stacking sequence of a glass/carbon hybrid composite and the effects of longitudinal fibers orientation and the incorporation of SiO2 nanoparticles were carefully investigated in this work. For the first time, the present research explores the effects of adding silicon dioxide (SiO2) nanoparticles on the tensile and flexural strength characteristics of glass-carbon hybrid composites with varying thicknesses and stacking sequences. Three fiber orientations were considered, i.e., 0°, 45°, and 90°, and SiO2 nanoparticles as epoxy reinforcement. The infusion procedure was used to fabricate the hybrid laminates. To understand and analyze the impacts of fiber orientation and SiO2 nanoparticles, mechanical parameters, such as tensile and flexural strength, were evaluated. The results showed that increasing plate thickness and the SiO2 nanoparticles boosted tensile and flexural strengths. The bending force was increased by 80.5% when 2 wt.% SiO2 nanoparticles were added to the epoxy for composites with 8 layers. For composite with 12 layers, the bending force increased by 62%.